Down‐regulation of exosomal microRNA‐224‐3p derived from bone marrow–derived mesenchymal stem cells potentiates angiogenesis in traumatic osteonecrosis of the femoral head. Issue 7 (9th April 2019) - Xu, Hai-Jia; Liao, Wen; Liu, Xiang-Zhong; Hu, Jing; Zou, Wen-Zhong; Ning, Yu; Yang, Yi; Li, Zhang-Hua
ABSTRACT: Traumatic osteonecrosis of the femoral head (ONFH) is a condition leading to the collapse of the femoral head, and the primary treatment is a total hip replacement, which has a poor prognosis. The current study was conducted with the aim of investigating the role of exosomes from bone marrow‐derived mesenchymal stem cells (BM‐MSCs) carrying microRNA‐224‐3p (miR‐224‐3p) in traumatic ONFH. Initially, a microarray analysis was performed to screen the differentially expressed genes and miRs associated with traumatic ONFH. Patients with traumatic and nontraumatic ONFH were enrolled, and HUVECs were obtained. The BM‐MSCs‐derived exosomes were purified and characterized, after which HUVECs were cocultured with exosomes. The functional role of miR‐224‐3p in traumatic ONFH was determined using ectopic expression, depletion, and reporter assay experiments. Endothelial cell proliferation, migration, invasion abilities, and angiogenesis were evaluated. Based on microarray analysis, miR‐224‐3p was found to be down‐regulated, whereas focal adhesion kinase family interacting protein of 200 kDa (FIP200) was up‐regulated in ONFH. Traumatic ONFH exosomes resulted in the up‐regulation of FIP200 and down‐regulation of miR‐224‐3p. FIP200 was confirmed to be a target gene of miR‐224‐3p. Exosomes were internalized by vascular endothelial cells. The down‐regulation of exosomal miR‐224‐3p was observed to promote endothelial cell proliferation, migration, invasion abilities, angiogenesis, and FIP200 expression. In addition, FIP200 overexpression promoted angiogenesis. In summary, the results highly indicated that lower miR‐224‐3p levels in exosomes derived from BM‐MSCs promote angiogenesis of traumatic ONFH by up‐regulating FIP200. The present study provides a potential strategy for the treatment of traumatic ONFH.—Xu, H.‐J., Liao, W., Liu, X.‐Z., Hu, J., Zou, W.‐Z., Ning, Y., Yang, Y., Li, Z.‐H. Down‐regulation of exosomal microRNA‐224‐3p derived from bone marrow‐derived mesenchymal stem cells potentiates angiogenesis in traumatic osteonecrosis of the femoral head. FASEB J. 33, 8055–8068 (2019). www.fasebj.org